Modeling: ratio between means of teaching and motor training in junior school physical education classes - Olha Ivashchenko; Sergii Iermakov; Oleg Khudolii (IP Iermakov S.S., 2021)
Background and Study Aim. The purpose of the study was to determine the ratio between means of teaching and motor training in junior school physical education classes. Materials and methods. The study involved 32 boys who were 8 years old at the beginning of the experiment. They were randomly divided into four groups of eight people each. A pedagogical experiment was conducted using a 22 full factorial design. The study recorded the following indicators: number of repetitions required to teach exercises; grade for a unidirectional movement coordination exercise (test 1); grade for a multidirectional movement coordination exercise (test 2); error in time accuracy of performing the squat thrust (test 3); error in time accuracy of 5 jumps on marks in 5 s (test 4); error in assessing muscular effort with visual control (test 5); vestibular stability, error (test 6). The obtained experimental material was processed statistically using statistical analysis software packages (SPSS 20). Results. According to the logistic function analysis, the achievement of an optimal result in differentiating temporal characteristics of movement requires 8.5 months, strength characteristics of movement - 8 months, movement coordination - 8 months, vestibular analyzer stability - 10 months. It takes 3 to 5 months to obtain positive increases in testing results in boys aged 8-9. The ratio of time allotted for strength training (ST) and coordination training (CT) to teaching motor actions (TMA) varies as 1:4 (ST: TMA) and 1:4.5 (CT: TMA). Conclusions. The ratio of time allotted for strength training, coordination training, and teaching to the time of the main part of the class ranges between 14.3-23.5% (strength training), 17.1-23.5% (coordination training), and 53.0-68.6% (teaching). As exercises become more complicated, the time allotted for strength and coordination training increases.